2010
DOI: 10.1080/13548501003623914
|View full text |Cite
|
Sign up to set email alerts
|

A profile of HIV risk factors in the context of sex work environments among migrant female sex workers in Beijing, China

Abstract: Migrant female sex workers (FSWs) are one of the most at-risk populations for HIV in China. This study demonstrates how multiple risk factors are situated and vary by types of sex work environments in a sample of 348 migrant FSWs in Beijing. Participants reported high rates of clients' refusal to use condoms (76%), unsafe sex with both clients (32%), non-paid regular partners (e.g., boyfriend or husband) (76%), and a STI symptom (79%) last year. Only 22% of FSWs had been tested for HIV. Risk factors were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 57 publications
5
68
2
3
Order By: Relevance
“…Stigma and discrimination were primary barriers to accessing sexually transmitted infection (STI) treatment and care among female sex workers in Nepal's Kathmandu Valley (Ghimire and van Teijlingen 2009). A study of migrant female sex workers in Beijing found that, due at least in part to structural barriers arising from criminalisation, less than half of the women were able to access healthcare to prevent and address STIs and/or health issues related to exposure to violence (Yi et al 2010). China's system of 're-education through labour' centres, in which female sex workers are administratively detained, has been shown to cause further social stigma and decrease the probability that detainees will be able to access needed services upon release (Tucker, Ren, and Sapio 2010).…”
Section: Criminalisationmentioning
confidence: 98%
“…Stigma and discrimination were primary barriers to accessing sexually transmitted infection (STI) treatment and care among female sex workers in Nepal's Kathmandu Valley (Ghimire and van Teijlingen 2009). A study of migrant female sex workers in Beijing found that, due at least in part to structural barriers arising from criminalisation, less than half of the women were able to access healthcare to prevent and address STIs and/or health issues related to exposure to violence (Yi et al 2010). China's system of 're-education through labour' centres, in which female sex workers are administratively detained, has been shown to cause further social stigma and decrease the probability that detainees will be able to access needed services upon release (Tucker, Ren, and Sapio 2010).…”
Section: Criminalisationmentioning
confidence: 98%
“…For the purpose of data analysis, these venues were categorized into three main types: entertainment (e.g., KTV and nightclubs), personal service (e.g., hair salons, sauna, and massage parlors) and street-based (e.g., streets and mini-hotels), following a similar classification system in previous studies (Yi et al, 2010).…”
Section: Sex Work Environmentsmentioning
confidence: 99%
“…Consequently, female migrants in China are frequently undereducated and underprepared for the increased opportunities to engage in sexual behavior that are available to them in urban settings (Huang et al, 2014). In the absence of skills, knowledge and services to promote sexual health, female migrants who relocate to large urban centers may experience risk for a range of health consequences, including unwanted pregnancy, unsafe termination of pregnancy and sexually transmitted infections (STIs) Yi et al, 2010;He et al, 2012). Some research has contrasted the more permissive norms related to premarital sex in large urban contexts versus norms in rural settings, which might also contribute to health risk behaviors among rural-to-urban migrants .…”
Section: Introductionmentioning
confidence: 99%